100 notable names from general practice - Metcalfe, Neil (Boca Raton : CRC Press, 2019)
This fascinating book presents 100 biographies of general practitioners, the majority of whom have made key contributions to the development of general practice and medicine, but also some who have influenced society through engineering, literature, music, politics, sport and other fields. Organised into four different time periods and with key themes in each, the reader will gain an insight into the background of these individuals and what led to their decision to enter the speciality, discover their successes and occasional failures, while also learning about significant events in the history of general practice, medical education, medical politics, medical research, the Royal College of General Practitioners and society as a whole. Key features: Highly readable and visual introduction to the history of general practice Includes 100 biographies of a variety of general practitioners from 1640 to the present day Describes both successes and failures in the development of the specialty and how these have helped direct and shape current clinical practice Key themes covered include academia and research, medical education, medical politics and society Ideal for anyone wishing to gain a broader insight into the history of this important specialty, as well as those interested in medical biography Written in an accessible style, and illustrated throughout, the book is an invaluable guide for academics, doctors or students with a special interest in general practice, medical education, medical history or social history.
OCLC-licensed vendor bibliographic record.
Keywords: Royal College of General Practitioners -- History; Physicians (General practice) -- Great Britain; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Alternative Medicine; MEDICAL / Atlases; MEDICAL / Essays; MEDICAL / Family & General Practice; MEDICAL / Holistic Medicine; MEDICAL / Osteopathy; MEDICAL / History; MEDICAL / Allied Health Services / General